Acquisition of extended-spectrum cephalosporin-resistant Gram-negative bacteria: epidemiology and risk factors in a 6-year cohort of 507 severe trauma patients. (December 2022) - Larcher, Romaric; Maury, Camille; Faivre, Guillaume; Dagod, Geoffrey; Dumont, Yann; Le Moing, Vincent; Villiet, Maxime; Capdevila, Xavier; Charbit, Jonathan
Highlights: Acquisition of antimicrobial resistance (AMR) was a prevalent complication in severe trauma patients AMR was mainly related to AmpC beta-lactamase producing Enterobacterales AMR acquisition was associated with mechanical ventilation, RRT, and exposure to cephalosporins +/- non-beta-lactam antibiotic ABSTRACT: Objectives: Severe trauma patients are at higher risk of infection and often exposed to antibiotics, which could favor acquisition of antimicrobial resistance. In this study, we aimed to assess prevalence, acquisition, and factors associated with acquisition of extended-spectrum cephalosporin-resistant Gram-negative bacteria (ESCR-GNB) in severe trauma patients. Methods: We conducted a retrospective monocentric cohort study in a French level one Regional Trauma Centre between 01 January 2010and 31 December 2015. Patients admitted for ≥ 7 days, with an Injury Severity Score ≥ 15, and ≥ 1 microbiological sample were included in the analysis. Prevalence and acquisition rate of ESCR-GNB were determined then, factors associated with ESCR-GNB acquisition were assessed using a Cox model. Results: Of 1873 patients admitted during the study period, 507 were included (median Injury Severity Score = 29 [22–34] and median intensive care unit length of stay = 16 days [10–28]). Most of them (450; 89%) had an antimicrobial therapy. Prevalence of ESCR-GNB increased from 13% to 33% during intensive care unit stay, bringing the ESCR-GNB acquisition rate to 29%. Acquisition of ESCR-GNB was mainly related to AmpC beta-lactamase Enterobacterales and was independently associated with mechanical ventilation needs (hazard ratio [HR] = 6.39; 95% confidence interval [CI] [1.51–27.17]; P = 0.01), renal replacement therapy needs (HR = 2.44; 95% CI [1.24–4.79]; P = 0.01), exposure to cephalosporins (HR = 1.06; 95% CI [1.01–1.12]; P = 0.02), and/or combination therapy with non-beta-lactam antibiotics such as vancomycin, linezolid, clindamycin, or metronidazole (HR = 1.03; 95% CI [1.01–1.06]; P = 0.02). Conclusions: Acquisition of ESCR-GNB was prevalent in severe trauma patients. Our results suggest selecting antibiotics with caution, particularly in the most severely ill.